(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Magnetic Abrasive Finishing (MAF) or super finishing is a modern unconventional finishing technique to produce high quality of parts, which is controlled by a magnetic energy. Magnetic abrasive operation develops some of the mechanical properties such as the surface quality. Nowadays, many of the traditional finishing technique such as honing, polishing and grinding are now being replaced by this process. In this review, principles of the MAF process, processing factors and their influence on the responses, the process modeling and development of the MAF method for flat surfaces will be examined in details research work in the literature. Additionally, there is a new type of MAF connected with Electrochemical Machining (ECM) to produce Electrochemical Magnetic Abrasive Machining (EMAM). The performance of models and multi-optimizing for predicting the responses such as metal removal rate (MRR), surface finish (SF), heat affected zone (HAZ) etc. are found to comparable in terms of the prediction accuracy and speed.